The effects of oral corticosteroids on lung function, type-2 biomarkers and patient-reported outcomes in stable asthma: A systematic review and meta-analysis. (November 2020) - Busby, John; Khoo, Esther; Pfeffer, Paul E.; Mansur, Adel H.; Heaney, Liam G.
Abstract: Background: Several studies have investigated the physiological effect of OCS in stable asthma, however these have included heterogeneous populations and outcomes. This paper is the first to combine their results. Methods: We searched Medline, Embase and Web of Science databases for studies reporting the impact of OCS on FEV1, FVC, blood eosinophils, fractional exhaled nitric oxide (FeNO), Asthma Control Questionnaire (ACQ) score or Asthma Quality Of Life Questionnaire (AQLQ) score in stable asthma. We extracted data on the correlates of OCS response. Results: 61 studies, comprising 1608 patients, were included. FEV1 was improved by 9% (95% CI: 7, 11). There were stronger increases in FEV1 among those with a mean baseline FEV1 <60% predicted (19%, 95% CI: 13, 24). Despite these improvements, substantial residual impairment remained after treatment. Blood eosinophils were reduced by 76% (95% CI: 63, 88) with larger decreases in studies of corticosteroid-naïve patients (93%, 95% CI: 73, 100). Sputum eosinophils were reduced by 89% (95% CI: 79, 98) while FeNO was decreased by 35% (95% CI: 28, 41). ACQ scores were reduced by 20% (95% CI: 11, 29). Patients with higher baseline lung function impairment, sputum eosinophils, blood eosinophils and FeNO had improved OCS response. Interpretation: OCS consistently improves lung function, reduces markers of type-2 inflammation, and alleviates asthma symptoms. However, substantial residual impairment remained following treatment and mean improvements were below the minimally important clinically difference. Patients with increased markers of type-2 inflammation are more responsive to treatment, suggesting these should be used to better target OCS use. Highlights: Oral corticosteroids consistently improved lung function, reduced type-2 inflammation, and alleviated asthma symptoms. Substantial residual impairment remained following treatment. Patients with increased markers of type-2 inflammation were more responsive to treatment.